Financialization, coalition of interests and interest rate in Brazil - Luiz Carlos Bresser-Pereira; Luiz Fernando de Paula; Miguel Bruno (Revue de la Régulation)
Studying the hypothesis of a pro-conservative monetary policy convention in Brazil, as initially formulated by Bresser-Pereira and Nakano (2002) and Erber (2011), we add three particular sub-hypotheses to it: (i) the prevalence of high real interest rates in Brazil for decades has led to the formation of a rentier-financial class coalition. Its aim is to maintain high real interest rates so as to gain from the resulting financialization process, fueled by interest revenues (ii) the existence of a “two-way“ public debt contagion effect between the banking reserves market and the public securities market; and (iii) the use of a high interest rate to finance current account deficits. To this end, the paper adopts as its starting point Keynes’s view of the interest rate as an eminently conventional phenomenon.